The ghost in the first row - Warner, Gertrude Chandler, 1890-1979. (Morton Grove, Ill. : A. Whitman, 2007)
The Aldens investigate the rumors of ghosts, disappearing props and a haunted seat in the Trap-Door Theater.
Keywords: Boxcar children (Fictitious characters) -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Orphans -- Juvenile fiction; Ghost stories